30-day journey with Julian of Norwich - Julian, of Norwich, 1343- (30-day journey series., 2021)
"Enrich each day with wisdom from our greatest spiritual thinkers. Through brief daily readings and reflections, the 30-Day Journey series invites readers to be inspired and transformed. By devoting a moment to meaningful reflection and spiritual growth, readers will find deeper understanding of themselves and the world, one day at a time.Valued since the fourteenth century for her spiritual insight, Julian of Norwich's powerful revelations remind us again and again of the power of divine love and that, with that love, all will be well. Whether you have long sought peace in her compelling words or are discovering her vision for the first time, this journey provides the perfect way to engage the thought of this beloved and wise mystic."--Publisher.